Use of Gamification Applications in Science Education - Hursen, Cigdem; Bas, Cizem (International Journal of Emerging Technologies in Learning (iJET), 2019)
In this research, the impact of gamification applications in science education on the science learning motivation of students has been determined and the opinions of students and parents on applications have been discussed. A total of 16 students and their parents partic-ipated in the study. The research was conducted on 4th grade primary students and em-ployed a mixed method consisting of both qualitative and quantitative elements. The moti-vation of students for learning science was obtained through quantitative data, whereas the opinions of students and parents on the usage of gamification applications were gathered through qualitative data. In the study, it was found that applications in science education created a positive impact on the learning motivation of students for science. Additionally, the research results also displayed that students and parents have positive opinions on the usage of gamification in science education.